Dispute Prevention and Dispute Resolution Post NAFTA: Choice of Law and Forum Selection Clauses - Talpis, Jeffrey (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 1995)
The following article describes the extent to which private parties to an international transaction in the free trade area may avoid disputes as to the law applicable to the contract and as to the court that would have the jurisdictional competency to hear disputes arising therefrom. As the study demonstrates serious limitations to the effectiveness of party autonomy, the author concludes that Government intervention is necessary to ensure a more favourable framework for international commercial transactions within the free trade area. The author also examines the growing use of alternative methods to resolve international disputes and makes a certain number of recommendations to improve and increase their use.